Visitor Comments about Botanic Parks and Gardens in the Context of Botanical Tourism - SALVARCI, Simge; AYLAN, F. Kubra (Journal of Tourism Management Research, 2021)
Botanical parks and gardens present different natural beauties together and allow the recognition of flora varieties. Within the scope of botanical tourism, botanical parks and gardens constitute one of the important visiting points of tourists. In this study, visitor comments on botanical parks / gardens are analyzed. Qualitative research method was used in the study. The study data consists of visitor comments on TripAdvisor website for "Ankara Botanical Park", "Atatürk Botanical Park", "Gaziantep Botanical Park", "Karaca Botanical Garden" and "Nezahat Gökyiğit Botanical Garden" in Turkey between May 2014 and November 2020. In the study, when the visitor's comments were evaluated, it was concluded that the comments on the botanical parks and gardens consisted of panoramic, peaceful / relaxing, lush place, nostalgic, natural wonder, tree museum codes. In addition to these, it was concluded that activities such as walking and sports, picnics, photographing, viewing the scenery, resting, and obtaining information about flora can be done by visitors in these parks and gardens.